Use of arable land with agroecological assessment of soils - Drebot, O.; Kudryk, А.; Savchuk, O. (Land Management, Cadastre and Land Monitoring, 2018)
Growing crop production with ignoring the quality of arable land leads to lower crop yields and unreasonable costs. There are areas of waterlogged, marshy, eroded soils or soil with low humus content and low available form for plant of nutrients in intensive use of land, that is leased or owned by modern agricultural companys. These lands have different area and configuration of soil contours and it is the cause of complicated planning of the fields’ boundaries. The purpose of representing data in this article is the justification of the rational use of arable land on condition detailed analysis of soil properties. Because the land management is the basis for optimization of agricultural production in a certain area. In order to obtain indicative results, the territory with complex structure of soil cover and with soils, which differ greatly in their physical and chemical properties and conditions of soil formation, was chosen as the object of research. Soil conditions were analyzed by natural indicators such us groundwater levels, granulometric composition of soil, nutrients concentration  that are available for plants, acidity of soils. The explored area has flat relief with moderate climate and insufficient humidification in separate periods. Soils’ parent material: alluvial deposits, loess loam, deluvial deposits. There are 11 groups of soils on the research area of 1272.4789 ha. Among them  Haplic Chernozem, Albic Luvisol, Gleyic Chernozem, Mollic Gleysol, Luvic Greyic Phaeozem, Endogleyic Arenosol and Histic Gleysol.  The Gleysols occupy a large area of surveyed land (106 hectares). These soils have a very poor water-air mode and suffer from drought or waterlogging  in some periods. In order to achieve the purpose of the work an existing methodology for the soils grouping into classes for the suitability of growing agricultural crops was used. Also the scale of soil evaluation for the Ruzhinsky agricultural region was applied. The article represents data of soil classification into classes of suitability by ten classification items. It is established that not the whole area of arable land is suitable for growing wheat. The estimated yield of winter wheat was calculated on the basis of soil's properties. Winter wheat is the  demanding plant to soil and climate condition. This is the cause there are low productivity of this plant on clay soil types and soils that have sandy granulometric composition. The estimated  yield of winter wheat on Histic Gleysol and Mollic Gleysol is 6.8 centner/ha and on Endogleyic Arenosol is 12.5 centner/ha. Inclusion such tapys of soils in fields area leads to a decrease the yield of winter wheat crops. This is difficult for land use in case low fertility soils are situated  in higher quality soils’ area. This situation is inherent  territory of Polisya and south part of  Ukrainian Lisostep zone. As a result of researchi it was realized that Haplic Gleysol  occupy small areas (between 0.1-0.3 ha). These soils are located near Endogleyic Arenosol that don’t suffer from excessive moisture and need another approach of  land use.The importance of taking into account the properties of soils is proved. The approach of land use of arable land is proposed.Keywords. Suitability of soils, groups of soils, wheat crop, land use.